Investor heterogeneity, investor-management disagreement and share repurchases - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2013)
This paper develops and tests a new theoretical explanation for stock repurchases. Investors may disagree with the manager about the firm's investment projects. A repurchase causes a change in the investor base as investors who are most likely to disagree with the manager tender their shares. Therefore, a firm is more likely to buy back shares when the level of investor-management agreement is lower, and agreement improves as a consequence. Moreover, dispersion of opinion among investors cannot explain repurchase activity once the stock price and investor-management agreement are controlled for. Overall, the evidence is consistent with firms strategically using repurchases to improve alignment between management and shareholders.